2012
DOI: 10.1186/gb-2012-13-4-r27
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and characterization of replication origins by deep sequencing

Abstract: BackgroundDNA replication initiates at distinct origins in eukaryotic genomes, but the genomic features that define these sites are not well understood.ResultsWe have taken a combined experimental and bioinformatic approach to identify and characterize origins of replication in three distantly related fission yeasts: Schizosaccharomyces pombe, Schizosaccharomyces octosporus and Schizosaccharomyces japonicus. Using single-molecule deep sequencing to construct amplification-free high-resolution replication profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
75
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 58 publications
8
75
0
5
Order By: Relevance
“…caused by underlying differences in the efficiencies of origins (Bechhoefer and Rhind, 2012;Rhind et al, 2010;Xu et al, 2012). Origin timing is a two-step process: the temporal programme is first determined early in the cell cycle (Dimitrova and Gilbert, 1999;Raghuraman et al, 1997), probably by establishing specific chromatin states around origins (see Box 2), and second, the time of origin firing during S phase is determined by the affinity of origins for limiting amounts of firing factors (Box 3).…”
Section: Box 1 the Establishment Of Origins Of Replicationmentioning
confidence: 99%
“…caused by underlying differences in the efficiencies of origins (Bechhoefer and Rhind, 2012;Rhind et al, 2010;Xu et al, 2012). Origin timing is a two-step process: the temporal programme is first determined early in the cell cycle (Dimitrova and Gilbert, 1999;Raghuraman et al, 1997), probably by establishing specific chromatin states around origins (see Box 2), and second, the time of origin firing during S phase is determined by the affinity of origins for limiting amounts of firing factors (Box 3).…”
Section: Box 1 the Establishment Of Origins Of Replicationmentioning
confidence: 99%
“…What defines origins in metazoans remains unclear. Origins are AT-rich in bacteria and yeast (Méchali 2010;Leonard and Méchali 2013) with a few exceptions (Xu et al 2012;Liachko et al 2014). Similarly, many origins in metazoans have AT-rich elements (Aladjem and Fanning 2004).…”
mentioning
confidence: 99%
“…The fission yeast Schizosaccharomyces pombe and the budding yeast Saccharomyces cerevisiae are two highly diverged model organisms widely used to study basic biological processes in eukaryotes (23). Although similar in size, S. pombe is distinguished from S. cerevisiae by sharing important characteristics of chromosome structure with metazoans, including relatively large chromosomes, numerous introns, large repetitive centromeres, low-complexity replication origins, the composition of chromatin remodeling complexes, and siRNA-regulated heterochromatin (24)(25)(26)(27). Recent micrococcal nuclease (MNase) mapping studies (16,28,29) revealed substantial differences between the two species in nucleosomal DNA sequence features and chromatin organization, including how histone-DNA sequence preferences affect nucleosome positioning and nucleosome occupancy patterns around transcription start sites (TSSs) and DNA replication origins.…”
mentioning
confidence: 99%